Competitive pressure by territorials promotes the utilization of unusual food source by subordinate ants in temperate European woodlands. Issue 5 (2nd September 2020) - Erős, Katalin; Maák, István; Markó, Bálint; Babik, Hanna; Ślipiński, Piotr; Nicoară, Roxana; Czechowski, Wojciech
Abstract : In the presence of territorial dominant ant species, lower-ranked ants change their foraging strategy by shifting their activity in time and space and by switching to suboptimal food sources. Although important for many insect species, pollen is a rarely used food source by ants. Occasional pollen consumption was demonstrated only in a handful of ant species that are mainly lower-ranked in the competitive hierarchy. We hypothesized that the consumption of pollen by subordinate ants might be enhanced by competitive pressure exerted by dominant species. In the frame of the current study, we assessed the food preference of ant species within a supercolony of the territorial wood ant Formica polyctena by offering them pollen and animal protein baits. Subordinate ant species, especially Myrmica ants, exploited both pollen and animal protein, while F. polyctena foraged only for animal protein. The Myrmica ants exploited pollen sources more intensively on plots where F. polyctena dominated animal protein baits, thus interspecific competition was stronger. As suggested by our study, under suboptimal conditions, where food availability is hindered, e.g. by the presence of superior competitors, pollen can, indeed, be used as a food source by subordinate ants.